Remarks on the taxonomic status of Jaera danubica Brtek, 2003 (Crustacea: Isopoda: Janiridae) - Borza, Péter (Zootaxa, 2012)
The representative of the genus Jaera Leach inhabiting continental waters throughout Europe has a rather complex taxonomic history. After discovering it in the River Tisza, Hungary, Dudich (1930) identified it as Jaera nordmanni (Rathke). This emerged to be a mistake, as the species was found to be identical with the subsequently described Jaera sarsi Valkanov (Kesselyák 1938). On the contrary, Veuille (1979) argued that the freshwater form is different from the brackish water species J. sarsi, and described it as a new species, J. istri Veuille, 1979. The new terminology has become widely used; however, recently the concept received criticism, implying that the characteristics distinguishing J. istri from J. sarsi fall within the confines of intraspecific variability (Tobias et al. 2005). Here I tentatively accept the latter point of view, and will refer to the species as J. sarsi in the following, but I also wish to point out that this matter could be settled using molecular methods.